Farmer participatory research on coconut diversity: Workshop report on methods and field protocols - Eyzaguirre, Pablo B.; Batugal, P. (International Institute of Plant Genetic Resources, 1999)
The contents of this report include the presentations, discussions and protocols produced at the Workshop on Farmer Participatory Research on Coconut Diversity held in both Davao, Philippines, 16 - 28 March 1998 and in Taveuni, Fiji, 24 - 28 March 1998. Two smaller follow up workshops were held in the Solomons and in Bangladesh, the results of which are also included. This volume provides documentation of a work in progress. It is intended as a reference for coconut scientists and development specialists in carrying out participatory field research with farmers. The contributors and participants welcome feedback and dialogue on approaches to foster greater participation of farmers in coconut research and conservation and greater recognition by scientists and development workers of the rich fund of knowledge on coconut diversity maintained by small-scale farmers.